2003
DOI: 10.1076/clin.17.2.170.16506
|View full text |Cite
|
Sign up to set email alerts
|

The Ecological Validity of Pediatric Neuropsychological Tests of Attention

Abstract: Neuropsychological tests are frequently used clinically to predict real-world, or adaptive functioning; however, there are too few data to support such predictions. The relationship between adaptive functioning and, in particular, attention tests, has not been documented. The present study sought to determine the association between several domains of attention and adaptive functioning in a heterogeneous clinical sample of 119 children. A significant omnibus canonical correlation (Rc=.54) indicated that attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…Consistent with this finding, Price et al (2003) found that neuropsychological measures of attention did not correlate with adaptive communication skills in a mixed pediatric clinical sample. They postulated that this might be because language rather than attention skills are more highly related to performance on the communication domain.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Consistent with this finding, Price et al (2003) found that neuropsychological measures of attention did not correlate with adaptive communication skills in a mixed pediatric clinical sample. They postulated that this might be because language rather than attention skills are more highly related to performance on the communication domain.…”
Section: Discussionmentioning
confidence: 55%
“…Attention dysfunction also may place this population at greater risk of adaptive impairments. In a pediatric clinical sample, neuropsychological measures of attention were shown to correlate with adaptive functioning, even when controlling for intelligence (Price, Joschko, & Kerns, 2003). Attention span has been found to mediate the relationship between time since the initiation of radiation treatment and daily living skills (Papazoglou, King, Morris, Morris, & Krawiecki, in press b).…”
mentioning
confidence: 99%
“…utvrđeno je da je, nezavisno od inteligencije, pažnja značajno povezana sa adaptivnim funkcionisanjem (Price, Joschko & Kerns, 2003). Pored toga, nalazi niza studija ukazuju na to da je kvalitet pažnje značajno povezan sa različitim domenima adaptivnog funkcionisanja u populaciji dece sa lakom intelektualnom ometenošću (LIO) (Buha i Gligorović, 2012 Iako postoji stav da se sa automatizacijom aktivnosti, koja se obično javlja u aktivnostima svakodnevnog živo-ta, angažman pažnje vremenom smanjuje, rezultati različitih istraživanja u kliničkoj populaciji ipak pokazuju da je pažnja značajno povezana i sa praktičnim veštinama, iako one u velikoj meri predstavljaju dobro usvojene, rutinske radnje.…”
Section: Gligorović M I Sar: Auditivna Pažnja I Praktične Adaptivnunclassified
“…No rezultati velikog broja istraživanja ukazuju na to da su problemi pažnje povezani sa teškoćama u sferi svakodnevnih aktivnosti i kod odraslih osoba sa mentalnim oboljenjima (za pregled istraživanja videti Silverstein, Menditto & Stuve, 2001). Aktivnosti svakodnevnog života zahtevaju niz samostalno iniciranih i ka cilju usmerenih postupaka, za šta je neophodna i pažnja, te, uprkos činjenici da je reč o dobro usvojenim rutinama, svaka od njih zahteva postavljanje cilja i usmereno ponaša-nje tokom određenog vremenskog perioda (Price et al, 2003).…”
Section: Gligorović M I Sar: Auditivna Pažnja I Praktične Adaptivnunclassified
“…Although a few studies have examined the relationship between "real life" skills and intelligence (Kahn, 1992), attention (Price, Joschko, & Kerns, 2003), and executive functions (Isquith, Gioia, & Espy, 2004), there has been less focus on the relationship between these daily life skills and neuropsychological measurement of skills considered to be dependent on temporal lobe integrity (e.g., visual perception or receptive language skills).…”
Section: Introductionmentioning
confidence: 99%